Building Inclusive Markets in Rural Bangladesh: How Intermediaries Work Institutional Voids - Mair, Johanna; Martí, Ignasi; Ventresca, Marc J. (Academy of Management Journal, 2012)
Much effort goes into building markets as a tool for economic and social development; those pursuing or promoting market building, however, often overlook that in too many places social exclusion and poverty prevent many, especially women, from participating in and accessing markets. Building on data from rural Bangladesh and analyzing the work of a prominent intermediary organization, we uncover institutional voids as the source of market exclusion and identify two sets of activities—redefining market architecture and legitimating new actors—as critical for building inclusive markets. We expose voids as analytical spaces and illustrate how they result from conflict and contradiction among institutional bits and pieces from local political, community, and religious spheres. Our findings put forward a perspective on market building that highlights the on-the-ground dynamics and attends to the institutions at play, to their consequences, and to a more diverse set of inhabitants of institutions.